Prinsip Fair and Equitable Treatment Sebagai Pembatas Host State Control Dalam Terminasi Kontrak Investasi - Azizah, Hasna (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Foreign investment plays a crucial role in national economic development, however, its implementation often involves tensions between the legal protection for investors and the host states’s sovereign right to control investment flows within its own jurisdiction in pursuit of national interests. To reconcile this potential conflict, Bilateral Investment Treaties (BITs) are established, to provide protection for foreign investors. These BITs incorporate the principle of Fair Equitable Treatment,which emphasize the host state’s obligation to act consistently, fairly and non-discriminatorily in regulating investments within its territory. This study analyzes the FET principle as a limitation on the host state authority to terminate investment contract. Using a normative juridical approach, this study examines the dynamics between a state's right to control foreign investment and the limitations imposed by the principle of Fair and Equitable Treatment. The results of this study provide a deeper understanding of Fair and Equitable Treatment, which function as a legal framework that ensures investor protection by encouraging host countries to implement transparency, due process, and fair treatment when terminating investment contracts.